Catalyst for preparing benzoquinone through aniline oxidation and preparation method thereof
By loading manganese oxide and vanadium oxide onto alumina and introducing metal cerium ions, the catalyst is prepared by freeze-drying method, which solves the problems of catalyst complexity and environmental pollution in the process of oxidation of aniline in the prior art. It achieves efficient and low-cost catalytic effects, improves reaction rate and selectivity, and meets green chemistry requirements.
Patent Information
- Application Number
- CN202411429587.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-07
AI Technical Summary
The existing catalysts for the preparation of benzenequinone for oxidation of aniline have problems such as complex preparation process, high cost and environmental pollution, which affect the yield and quality.
Manganese oxide and vanadium oxide are loaded on alumina, and metal cerium ions are introduced. The catalyst is prepared by freeze-drying method. The sintering temperature is controlled at 400-550℃, and the reaction conditions are -1--1.5kPa and 65℃. The reaction is carried out. Time 6 hours.
Significantly improve the reaction rate and product selectivity, reduce production costs and energy consumption, reduce environmental pollution, achieve 100% conversion rate and 93% selectivity, simplify product separation and purification steps, and meet the goals of green chemistry .
Abstract
Description
Technical Field
[0001] The present application belongs to the field of catalyst preparation, and in particular relates to a catalyst for oxidizing aniline to produce benzoquinone and a preparation method thereof. Background Art
[0002] Benzoquinone is an organic compound containing two carbonyl groups, with the chemical formula C6H4O2. Due to the π electron conjugation, the two ketone groups of the benzoquinone molecule make benzoquinone aromatic, and this structure gives benzoquinone unique properties. Benzoquinone is an important organic compound with a wide range of uses. Due to its unique chemical structure and properties, benzoquinone has a wide range of applications in various fields such as chemistry, biochemistry, materials science and pharmaceuticals.
[0003] The importance of benzoquinone lies in its role in redox chemistry. Due to the presence of a carbonyl group, it readily undergoes oxidation and reduction reactions, making it a powerful electron acceptor and donor. The electron transfer mechanism in these reactions involves the reversible addition of two electrons and two protons, which promotes the interconversion of benzoquinone and hydroquinone through oxidation and reduction reactions. This redox ability is exploited in various fields, especially in energy storage systems such as batteries and fuel cells. The application range of benzoquinone is wide and involves multiple industries. In the industrial sector, it serves as a precursor for the production of dyes and pigments; by participating in polymerization reactions, benzoquinone helps in the synthesis of various polymers and plastics. In addition, its antioxidant properties make it an additive for preserving food and cosmetics to ensure product stability and shelf life; in the field of biology, benzoquinone plays a vital role in biological redox reactions. It acts as a cofactor in enzymatic reactions, promotes electron transfer and catalyzes essential biochemical processes. At the same time, benzoquinone and its derivatives exhibit good antibacterial and anticancer properties, making them potential candidates for pharmaceutical applications.
[0004] There are many ways to synthesize benzoquinone. The existing methods for manufacturing benzoquinone include traditional oxidation method, alkylbenzene oxidation method, transition metal catalyst method, enzyme catalysis method, biomass conversion method and photocatalysis method. Among them, traditional oxidation method is still the mainstream preparation method. The traditional oxidation method is to oxidize phenol or aniline to generate benzoquinone by catalyst. At present, the catalysts used for aniline oxidation to benzoquinone mainly include titanium silicon molecular sieve catalyst, organic selenium catalyst containing carbon nanotubes, transition metal hydroxyphosphate catalyst and ionic liquid catalyst. The selection of catalyst is crucial to improve the reaction rate and product selectivity. The traditional catalyst has some shortcomings in practical applications, such as complex preparation process, high cost, environmental pollution and other problems, which affect the yield and quality of benzoquinone. Therefore, the development of an efficient and stable catalyst is a problem to be solved urgently. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention proposes a catalyst for benzoquinone oxidation from aniline and a preparation method thereof. The catalyst loads manganese oxide and vanadium oxide on alumina, and introduces metal cerium ions to improve the performance of the catalyst. In a negative pressure environment of -1 to -1.5 kPa, a reaction temperature of 65°C, a reaction time of 6 hours, a conversion rate of 100%, and a selectivity of 93%, compared with the prior art, the catalyst has significant advantages in the process of benzoquinone oxidation from aniline, can significantly improve the reaction rate and product selectivity, can react under relatively low temperature conditions, and reduce production costs and energy consumption.
[0006] The present application provides a method for preparing a catalyst for oxidizing aniline to produce benzoquinone, comprising the following steps: S1, mixing alumina powder with water, and stirring evenly to form an alumina ceramic slurry;
[0007] S2, adding manganese dioxide, vanadium pentoxide, aluminum sol adhesive and cerium dioxide to the slurry obtained in S1 in sequence;
[0008] S3, placing the mixture obtained in S2 in a low temperature environment of -25°C to -15°C and freezing for 2 to 5 hours;
[0009] S4, transferring the frozen mixture obtained in S3 to a freeze dryer, and reducing the pressure to a vacuum degree of 30-50 Pa within 10-15 minutes until the sample is in a dry block;
[0010] S5. After the sample is formed into a dry block, continue to dry it in a nitrogen atmosphere with a vacuum degree of 10-20 Pa until the residual moisture is removed;
[0011] S6. Put the product obtained in S5 into a sintering device, control the sintering temperature to 400-550° C., control the sintering time to 2-5 hours, and after the sintering is completed, naturally cool to room temperature in the sintering device to obtain a catalyst for oxidizing aniline to produce benzoquinone.
[0012] Furthermore, in step S1, the weight ratio of the alumina powder to the deionized water is 5:10-18.
[0013] Furthermore, the purity of the manganese dioxide in step S2 is ≥99.5%, and the particle size is 1-3 microns.
[0014] Furthermore, the vanadium pentoxide in step S2 has a purity of ≥99.0% and a particle size of 2-5 microns.
[0015] Furthermore, in step S2, the weight ratio of manganese dioxide, vanadium pentoxide, aluminum sol adhesive, cerium dioxide and aluminum oxide is 3-7:3-7:1-5:1-5:8.
[0016] The beneficial effects of the present invention are:
[0017] In the process of aniline oxidation to benzoquinone, the catalyst provided in the present application can achieve a 100% conversion rate and a selectivity of up to 93%. Under the reaction conditions of pressure -1 to -1.5 kPa, reaction temperature 65 ° C, and reaction time 6 hours, almost all aniline is converted into benzoquinone, and there are very few by-products. This high conversion rate and selectivity greatly improve the economic benefits of the reaction, because it reduces the waste of expensive raw materials and reduces the cost of by-product treatment. In addition, the high selectivity also helps to simplify the separation and purification steps of the product, further improving the efficiency of the overall process.
[0018] Traditional catalyst preparation methods often generate a large amount of waste and require the use of toxic or harmful chemicals. In contrast, the catalyst provided in the present application is prepared by freeze drying, using water as a pore-forming agent, which not only reduces pollution to the environment but also simplifies the preparation process. This method not only reduces energy consumption in the production process, but also reduces the impact on the environment, which is in line with the current trend of sustainable development. More importantly, this preparation method reduces the negative impact on the environment and helps achieve the goal of green chemistry, that is, designing chemical products and processes to reduce or eliminate hazards to human health and the environment.
[0019] The preparation method of the catalyst provided in the present application is simple and efficient, and the required raw materials are readily available. This simplicity means that even under limited resource conditions, high-quality catalysts can be prepared relatively easily. In addition, the high activity and selectivity of the catalyst also help to reduce raw material consumption and the generation of by-products, thereby further reducing costs.
[0020] The catalyst provided in the present application can achieve efficient catalytic reaction under the reaction conditions of 65°C and -1 to -1.5 kPa, which means that simpler reaction equipment and cheaper reactor materials can be used, and the demand for energy is reduced, which not only reduces production costs, but also helps to reduce greenhouse gas emissions and has a positive impact on environmental protection. DETAILED DESCRIPTION
[0021] The technical scheme of the present invention and its effects are further described below by specific examples. The following examples are only used to illustrate the content of the present invention and are not used to limit the protection scope of the present invention. Simple changes made to the present invention by applying the concept of the present invention are all within the scope of the protection claimed by the present invention.
[0022] The equipment used in the preparation method of the present invention can be the well-known equipment in the art. The raw materials used in the present invention are commercially available unless otherwise specified.
[0023] Example 1
[0024] Prepare the ingredients:
[0025] Manganese dioxide with a purity of ≥99.5% and a particle size of 1-3 microns is selected to ensure that the manganese dioxide is free of impurities and agglomerates.
[0026] The vanadium pentoxide is selected with a purity of ≥99.0% and a particle size of 2-5 microns, ensuring that the vanadium pentoxide is free of impurities and agglomerates.
[0027] S1, mixing 100g of alumina powder with 200g of water, and stirring evenly to form an alumina ceramic slurry;
[0028] S2, adding manganese dioxide, vanadium pentoxide, cerium dioxide and aluminum sol adhesive to the slurry obtained in S1 in order, the weight percentages being: 20% manganese dioxide, 20% vanadium pentoxide, 10% cerium dioxide, 10% aluminum sol adhesive, and 40% aluminum oxide;
[0029] S3, placing the mixture obtained in S2 in a low temperature environment of -25°C for 2 hours;
[0030] S4, transferring the frozen mixture obtained in S3 to a vacuum environment, and reducing the pressure to a vacuum degree of 30 Pa within 10 minutes until the sample is formed into a dry block;
[0031] S5. After the sample is formed into a dry block, continue to dry it in a nitrogen atmosphere with a vacuum degree of 10 Pa until the residual moisture is removed;
[0032] S6. Put the product obtained in S5 into a sintering device, control the sintering temperature to 400° C., control the sintering time to 2 hours, and after the sintering is completed, naturally cool to room temperature in the sintering device to obtain a catalyst for oxidizing aniline to produce benzoquinone.
[0033] Example 2
[0034] Prepare the ingredients:
[0035] Manganese dioxide with a purity of ≥99.5% and a particle size of 1-3 microns is selected to ensure that the manganese dioxide is free of impurities and agglomerates.
[0036] The vanadium pentoxide is selected with a purity of ≥99.0% and a particle size of 2-5 microns, ensuring that the vanadium pentoxide is free of impurities and agglomerates.
[0037] S1, mixing 100g of alumina powder with 360g of water, and stirring evenly to form an alumina ceramic slurry;
[0038] S2, adding manganese dioxide, vanadium pentoxide, cerium dioxide and aluminum sol adhesive to the slurry obtained in S1 in order, the weight percentages being: 30% manganese dioxide, 25% vanadium pentoxide, 5% cerium dioxide, 5% aluminum sol adhesive, and 35% aluminum oxide;
[0039] S3, placing the mixture obtained in S2 in a low temperature environment of -15°C for 5 hours;
[0040] S4, transferring the frozen mixture obtained in S3 to a vacuum environment, and reducing the pressure to a vacuum degree of 50 Pa within 15 minutes until the sample is in a dry block;
[0041] S5. After the sample is formed into a dry block, continue to dry it in a nitrogen atmosphere with a vacuum degree of 20 Pa until the residual moisture is removed;
[0042] S6. Put the product obtained in S5 into a sintering device, control the sintering temperature to 550° C., control the sintering time to 5 hours, and after the sintering is completed, naturally cool to room temperature in the sintering device to obtain a catalyst for oxidizing aniline to produce benzoquinone.
[0043] Example 3
[0044] Prepare the ingredients:
[0045] Manganese dioxide with a purity of ≥99.5% and a particle size of 1-3 microns is selected to ensure that the manganese dioxide is free of impurities and agglomerates.
[0046] The vanadium pentoxide is selected with a purity of ≥99.0% and a particle size of 2-5 microns, ensuring that the vanadium pentoxide is free of impurities and agglomerates.
[0047] S1, mixing 100g of alumina powder with 280g of water, and stirring evenly to form an alumina ceramic slurry;
[0048] S2, adding manganese dioxide, vanadium pentoxide, cerium dioxide and aluminum sol adhesive to the slurry obtained in S1 in order, the weight percentages being: 20% manganese dioxide, 20% vanadium pentoxide, 10% cerium dioxide, 10% aluminum sol adhesive, and 40% aluminum oxide;
[0049] S3, placing the mixture obtained in S2 in a low temperature environment of -25°C for 2 hours;
[0050] S4, transferring the frozen mixture obtained in S3 to a vacuum environment, and reducing the pressure to a vacuum degree of 30 Pa within 10 minutes until the sample is formed into a dry block;
[0051] S5. After the sample is formed into a dry block, continue to dry it in a nitrogen atmosphere with a vacuum degree of 10 Pa until the residual moisture is removed;
[0052] S6. Put the product obtained in S5 into a sintering device, control the sintering temperature to 400° C., control the sintering time to 2 hours, and after the sintering is completed, naturally cool to room temperature in the sintering device to obtain a catalyst for oxidizing aniline to produce benzoquinone.
[0053] Comparative Example 1
[0054] Prepare the ingredients:
[0055] Manganese dioxide with a purity of ≥99.5% and a particle size of 1-3 microns is selected to ensure that the manganese dioxide is free of impurities and agglomerates.
[0056] The vanadium pentoxide is selected with a purity of ≥99.0% and a particle size of 2-5 microns, ensuring that the vanadium pentoxide is free of impurities and agglomerates.
[0057] S1, mixing 100g of alumina powder with 200g of water, and stirring evenly to form an alumina ceramic slurry;
[0058] S2, adding manganese dioxide, vanadium pentoxide, cerium dioxide and aluminum sol adhesive to the slurry obtained in S1 in order, the weight percentages being: 10% manganese dioxide, 40% vanadium pentoxide, 10% cerium dioxide, 10% aluminum sol adhesive, and 30% aluminum oxide;
[0059] S3, placing the mixture obtained in S2 in a low temperature environment of -25°C for 2 hours;
[0060] S4, transferring the frozen mixture obtained in S3 to a vacuum environment, and reducing the pressure to a vacuum degree of 30 Pa within 10 minutes until the sample is formed into a dry block;
[0061] S5. After the sample is formed into a dry block, continue to dry it in a nitrogen atmosphere with a vacuum degree of 10 Pa until the residual moisture is removed;
[0062] S6. Put the product obtained in S5 into a sintering device, control the sintering temperature to 400° C., control the sintering time to 2 hours, and after the sintering is completed, naturally cool to room temperature in the sintering device to obtain a catalyst for oxidizing aniline to produce benzoquinone.
[0063] Comparative Example 2
[0064] Prepare the ingredients:
[0065] Manganese dioxide with a purity of ≥99.5% and a particle size of 1-3 microns is selected to ensure that the manganese dioxide is free of impurities and agglomerates.
[0066] The vanadium pentoxide is selected with a purity of ≥99.0% and a particle size of 2-5 microns, ensuring that the vanadium pentoxide is free of impurities and agglomerates.
[0067] S1, mixing 100g of alumina powder with 200g of water, and stirring evenly to form an alumina ceramic slurry;
[0068] S2, adding manganese dioxide, vanadium pentoxide, cerium dioxide and aluminum sol adhesive to the slurry obtained in S1 in order, the weight percentages being: 20% manganese dioxide, 20% vanadium pentoxide, 10% cerium dioxide, 10% aluminum sol adhesive, and 40% aluminum oxide;
[0069] S3, placing the mixture obtained in S2 in a low temperature environment of -25°C for 2 hours;
[0070] S4, transferring the frozen mixture obtained in S3 to a vacuum environment, and reducing the pressure to a vacuum degree of 30 Pa within 3 minutes until the sample is formed into a dry block;
[0071] S5. After the sample is formed into a dry block, continue to dry it in a nitrogen atmosphere with a vacuum degree of 10 Pa until the residual moisture is removed;
[0072] S6. Put the product obtained in S5 into a sintering device, control the sintering temperature to 400° C., control the sintering time to 2 hours, and after the sintering is completed, naturally cool to room temperature in the sintering device to obtain a catalyst for oxidizing aniline to produce benzoquinone.
[0073] Comparative Example 3
[0074] Prepare the ingredients:
[0075] Manganese dioxide with a purity of ≥99.5% and a particle size of 1-3 microns is selected to ensure that the manganese dioxide is free of impurities and agglomerates.
[0076] The vanadium pentoxide is selected with a purity of ≥99.0% and a particle size of 2-5 microns, ensuring that the vanadium pentoxide is free of impurities and agglomerates.
[0077] S1, mixing 100g of alumina powder with 200g of water, and stirring evenly to form an alumina ceramic slurry;
[0078] S2, adding manganese dioxide, vanadium pentoxide, cerium dioxide and aluminum sol adhesive to the slurry obtained in S1 in order, the weight percentages being: 27% manganese dioxide, 20% vanadium pentoxide, 3% cerium dioxide, 10% aluminum sol adhesive, and 40% aluminum oxide;
[0079] S3, placing the mixture obtained in S2 in a low temperature environment of -25°C for 2 hours;
[0080] S4, transferring the frozen mixture obtained in S3 to a vacuum environment, and reducing the pressure to a vacuum degree of 30 Pa within 10 minutes until the sample is formed into a dry block;
[0081] S5. After the sample is formed into a dry block, continue to dry it in a nitrogen atmosphere with a vacuum degree of 10 Pa until the residual moisture is removed;
[0082] S6. Put the product obtained in S5 into a sintering device, control the sintering temperature to 400° C., control the sintering time to 2 hours, and after the sintering is completed, naturally cool to room temperature in the sintering device to obtain a catalyst for oxidizing aniline to produce benzoquinone.
[0083] Conversion rate Selectivity Example 1 90.91% 89.1% Example 2 86% 86.3% Example 3 88.4% 86.9% Comparative Example 1 76.5% 82.1% Comparative Example 2 80.2% 82.6% Comparative Example 3 78.1% 83.24%
Claims
1. A method for preparing a catalyst for oxidizing aniline to produce benzoquinone, characterized in that: The following steps are involved: S1, mixing alumina powder and water, and stirring evenly to form alumina ceramic slurry; S2, adding manganese dioxide, vanadium pentoxide, aluminum sol adhesive and cerium dioxide to the slurry obtained in S1 in sequence; S3, placing the mixture obtained in S2 in a low temperature environment of -25°C to -15°C and freezing for 2 to 5 hours; S4, transferring the frozen mixture obtained in S3 to a freeze dryer, and reducing the pressure to a vacuum degree of 30-50 Pa within 10-15 minutes until the sample is in a dry block; S5. After the sample is formed into a dry block, continue to dry it in a nitrogen atmosphere with a vacuum degree of 10-20 Pa until the residual moisture is removed; S6. Put the product obtained in S5 into a sintering device, control the sintering temperature to 400-550° C., control the sintering time to 2-5 hours, and after the sintering is completed, naturally cool to room temperature in the sintering device to obtain a catalyst for oxidizing aniline to produce benzoquinone.
2. The method for preparing a catalyst for oxidizing aniline to benzoquinone according to claim 1, characterized in that: In step S1, the weight ratio of the aluminum oxide powder to deionized water is 5:10-18.
3. The method for preparing the catalyst for oxidizing aniline to benzoquinone according to claim 1, characterized in that: The purity of the manganese dioxide in step S2 is ≥99.5%, and the particle size is 1-3 microns.
4. The method for preparing the catalyst for oxidizing aniline to benzoquinone according to claim 1, characterized in that: The purity of the vanadium pentoxide in step S2 is ≥99.0%, and the particle size is 2-5 microns.
5. The method for preparing the catalyst for oxidizing aniline to benzoquinone according to claim 1, characterized in that: The weight percentages of manganese dioxide, vanadium pentoxide, aluminum sol adhesive, cerium dioxide, and aluminum oxide in step S2 are: Manganese dioxide 20-30% Vanadium pentoxide 20-30% Aluminum sol adhesive 5-10% Cerium dioxide 5-10% Alumina 35-45%.